2014
DOI: 10.1080/07481187.2014.946627
|View full text |Cite
|
Sign up to set email alerts
|

Common Therapeutic Factors in Bereavement Groups

Abstract: Group therapy remains a popular treatment format for individuals experiencing bereavement. Although many innovative group treatments for grief are being developed, common therapeutic factors can also contribute to outcomes. The author integrates research on group therapy processes and treatment for grief, and examines evidence regarding group therapeutic factors that may influence bereavement group outcomes. Specifically, research on therapeutic factors related to sharing and support, interpersonal learning, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, the support groups for the young adults included functions such as forming bonds with, sharing and supporting others in similar situation, which is likely to affect their psychosocial well-being. 58 This reasoning is furthermore consistent with the ecological systems theory, 84 which argues that all changes in systems, such as participating in support groups, affect the individual. The wider research on the effects of support are inconclusive.…”
Section: Sample Reflectionssupporting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, the support groups for the young adults included functions such as forming bonds with, sharing and supporting others in similar situation, which is likely to affect their psychosocial well-being. 58 This reasoning is furthermore consistent with the ecological systems theory, 84 which argues that all changes in systems, such as participating in support groups, affect the individual. The wider research on the effects of support are inconclusive.…”
Section: Sample Reflectionssupporting
confidence: 76%
“…57 Despite clear indication that support should be given to those with the most complex needs, it has been suggested that support can also have therapeutic factors for those who experience normal grief, in that it improves well-being, such as self-esteem, anxiety and depression. 58 Rice 58 has proposed that the most common therapeutic factors may be divided into three groups. The first group concerns support that contributes to cohesion by the interrelations in the group, promoting universality by sharing experiences with others in a similar situation and altruism by supporting others.…”
Section: Support In Bereavementmentioning
confidence: 99%
See 1 more Smart Citation
“…This gender difference is important because some studies reported that men were less frequently provided with the opportunities to process their feelings (26). Evidence suggests that bereaved individuals need social support during the bereavement process (27) as well as to make meaning of their loss (28) in order to work through grief. Bearing in mind that bereaved persons have been found to underuse mental health services (29), it is essential that psychological support be offered regardless of whether bereaved persons expressed willingness to seek professional help.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen group therapist skills were extracted from this review (Table 1). 31 Therapeutic alliance, Empathy, Goal consensus/Collaboration, Group cohesion Rice, 2015 32 Sharing, Support, Interpersonal learning, Meaning-making Gallagher, 2014 33 Self-perceptions through feedback Ahmed, 2010 34 Catharsis, Group cohesiveness, Interpersonal learning Kennard, 1987 35 Acceptance, Learning from interpersonal action, Self-disclosure, Catharsis, Guidance…”
Section: Literature Searchmentioning
confidence: 99%